Apocalypse (Not) Now - Lütticken, Sven Lütticken (The Nordic Journal of Aesthetics, 2016)
From its beginning in the 1940s, the nuclear regime has been the subject of aesthetic as well as political practices and interventions. This article examines a number of such interventions, from the Surrealists via the Situationists to the present. The focus is on forms of aesthetic activism that challenges the reigning thanatocracy. Key figures are Roberto Matta and Wolfgang Paalen (as “first responders” in the 1940s), Situationists such as Debord and Vaneigem in the late 1950s and 1960s (effecting a repoliticization of avant-garde aesthetics), later writings by ex-Situationists and pro-Situs such as René Riesel and Jaime Semprun, as well as contemporary artists such as Ei Arakawa and The Otolith Group (and their responses to Fukushima). Through concepts and tropes such as invisibility, survival and mutation, these practitioners seek to counteract the “insensible” nature of radiation and problematize post-war society’s dependency on nuclear deterrence and “peaceful” nuclear technology alike.